2004
DOI: 10.1111/j.1365-2141.2004.04873.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell recognition of bcr/abl in healthy donors and in patients with chronic myeloid leukaemia

Abstract: Summary In chronic myeloid leukaemia (CML), peptides from the fusion region of bcr3/abl2 are likely to play a role in anti‐leukaemic T cell immunity. We investigated whether T cells that recognize bcr/abl fusion peptides could be detected in healthy donors and CML patients. T cell responses against bcr3/abl2 fusion peptides were analysed by γ‐interferon enzyme‐linked immunospot assays after prestimulation of peripheral blood mononuclear cells in the presence of anti‐CD3‐antibodies and interleukin‐2. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…In both cases, the HLA‐B8 binding tetramer (GFKQSSKAL) was positive but T‐cell frequency was close to the detection limit. In contrast, after prestimulation with CD3 antibody and IL‐2, as previously reported (Westermann et al , 2004), tetramer staining was positive in four of eight patients, in all cases it was the HLA‐B8 (GFKQSSKAL) tetramer which detected leukaemia‐reactive T cells (see Fig 1 and Table I).…”
Section: Peptide‐specific T‐cell Responses In Chronic Myeloid Leukaemsupporting
confidence: 82%
See 1 more Smart Citation
“…In both cases, the HLA‐B8 binding tetramer (GFKQSSKAL) was positive but T‐cell frequency was close to the detection limit. In contrast, after prestimulation with CD3 antibody and IL‐2, as previously reported (Westermann et al , 2004), tetramer staining was positive in four of eight patients, in all cases it was the HLA‐B8 (GFKQSSKAL) tetramer which detected leukaemia‐reactive T cells (see Fig 1 and Table I).…”
Section: Peptide‐specific T‐cell Responses In Chronic Myeloid Leukaemsupporting
confidence: 82%
“…Recently, we have reported on T cells specifically recognising the bcr3/abl2 fusion region in CML patients in complete cytogenetic response and in some healthy individuals using a prestimulation protocol with CD3 antibodies and interleukin (IL)‐2 (Westermann et al , 2004). In the present study, we have used a novel T‐cell assay for the simultaneous detection of different cytokines by cytometric bead array (CBA) in blood samples from CML patients.…”
Section: Peptide‐specific T‐cell Responses In Chronic Myeloid Leukaemmentioning
confidence: 99%
“…In recent decades, there has been an increasing evidence from both preclinical and clinical studies that the human T‐cell repertoire contains leukaemia‐reactive T cells, which might be of clinical relevance (Chen et al , 1992; Bocchia et al , 1996; Yotnda et al , 1998; Molldrem et al , 2000, 2003; Bellantuono et al , 2002; Westermann et al , 2004, 2005). Several leukaemia‐associated antigens, such as proteinase‐3 (and particularly its peptide PR‐1) (Molldrem et al , 2000), Wilms Tumor Protein‐1 (WT‐1) (Bellantuono et al , 2002) and bcr/abl (Chen et al , 1992; Bocchia et al , 1996), have been identified and may serve as target for T cells.…”
mentioning
confidence: 99%
“…However, the same group described selective deletion of high‐affinity T cells from the T‐cell repertoire of CML patients, which may partially explain the failure of the immune system to eradicate the malignant cell clone (Molldrem et al , 2003). T‐cell responses against WT‐1‐ and bcr/abl have been described by several groups (Chen et al , 1992; Bocchia et al , 1996; Yotnda et al , 1998; Osman et al , 1999; Norbury et al , 2000; Clark & Christmas, 2001; Bellantuono et al , 2002; Westermann et al , 2004, 2005), but their activity in vivo remains a matter of debate. Clinical relevance of immunity against bcr/abl is also suggested by epidemiological data of Posthuma et al (1999), which showed that coexpression of human leucocyte antigen (HLA)‐A3 and –B8 (both HLA molecules can efficiently present immunogenic peptides from the bcr3/abl2 fusion region) reduces the risk of acquiring CML by approximately 50%.…”
mentioning
confidence: 99%
“…13,14 A proteína quimérica resultante da fusão bcrabl apresenta uma atividade tirosina-quinase elevada, responsável pela patogênese da doença. 15 O neogene bcr-abl é o responsável pelo processo molecular que determina a transformação da célula progenitora hematopoética normal em maligna. A célula leucêmica bcrabl apresenta uma mieloproliferação contínua resultante, provavelmente, de três mecanismos principais: alteração da adesão das células progenitoras às células estromais e à matriz extracelular, 16 manutenção de um sinal mitogênico constante 17 e resistência à apoptose celular.…”
unclassified